Planktonic crustaceans of the Balkhash-Alakol lake system (South-Eastern Kazakhstan) - Kenzheyeva, Akerke; Krupa, Elena G. (Acta Biologica Sibirica, 2025)
Planktonic crustaceans are the basis of the food supply for animals with higher trophic levels and determine the fish productivity of any water body. Large Cladocera play a significant role in the natural purification of the water column. Some Copepods are intermediate hosts of parasites, including those that are dangerous to humans. Given the key role of planktonic invertebrates, their research is essential for effective management of aquatic ecosystems. The Balkhash-Alakol system includes five main lakes (Balkhash, Alakol, Koshkarkol, Sasykkol, and Zhalanashkol), with a pronounced gradient of water mineralization. The study of planktonic crustaceans in the lakes of the Balkhash-Alakol system was carried out between 2002 and 2007. Previous studies addressed zooplankton; however, planktonic crustaceans were not studied separately, making this research necessary. The samples and the processing of the zooplankton samples were performed using standard methods. During the study, 74 planktonic crustaceans were recorded, with the highest species richness in the East Balkhash and Alakol lakes (48–47 species) and the lowest values in Zhalanashkol (9 species). According to the results of the cluster analysis, the species composition of planktonic crustaceans in the lakes surveyed was characterized by a low level of similarity. Ecologically, euryhaline forms predominated throughout. The abundance of planktonic crustaceans ranged from 31,836 to 105,860 individuals/m³. The dominant species included Diaphanosoma lacustris, Mesocyclops leuckarti, Thermocyclops crassus, Arctodiaptomus salinus, and Ceriodaphnia reticulata. The results obtained expand our understanding of the formation of the structure of plankton communities under the influence of external factors.